Аналіз молекулярних механізмів розвитку експериментального цукрового діабету в щурів лінії Вістар за умов впливу переривчастої гіпоксії - Іваненко, Тарас Васильович; Ivanenko, T. V. (Запорізький державний медико-фармацевтичний університет, 2023)
Мета роботи – у зразках тканин підшлункової залози щурів лінії Вістар визначити зміни в експресії генів, що пов’язані з перебігом цукрового діабету, за умов впливу переривчастої гіпоксії. Матеріали та методи. Аналіз експресії генів виконали за допомогою методу полімеразної ланцюгової реакції (ПЛР) зі зворотною транскрипцією в режимі реального часу за допомогою набору RT2 Profiler™ PCR Array Rat Diabetes (QIAGEN, Німеччина). Досліджували підшлункову залозу експериментальних тварин. Результати. У результаті ПЛР-дослідження тварин з експериментальним цукровим діабетом і при впливі на його перебіг гіпоксичних тренувань визначили такий розподіл активності генів, що вивчали: гени з низькою експресією порівняно з контрольною групою тварин, де ΔΔCт <30 (Ace; Cd28; Ctla4; Dusp4; Enpp1; Foxp3; G6pc; Gcgr; Glp1r; Gpd1; Gsk3b; Hmox1; Ide; Ikbkb; Il10; Il6; Ins1; Nfkb1; Nkx2-1; Parp1; Pdx1; Pik3cd; Pik3r1; Ppargc1a; Ptpn1; Rab4a; Retn; Slc14a2; Snap25; Sod2; Stx4; Stxbp1; Stxbp2; Tnf; Tnfrsf1a; Tnfrsf1b; Ucp2; Vamp2; Vegfa); гени, в яких не виявлені достовірні зміни в зразках щодо контрольної групи (Acly; Adra1a; Adrb3; Agt; Akt2; Aqp2; Ccl5; Ccr2; Ceacam1; Cebpa; Dpp4; Fbp1; Foxc2; Foxg1; Gcg; Gck; Hnf1b; Hnf4a; Icam1; Ifng; Igfbp5; Il12b; Il4r; Inppl1; Irs1; Irs2; Mapk14; Mapk8; Neurod1; Nos3; Nrf1; Nsf; Ppara; Pparg; Pygl; Sell; Serpine1; Slc2a4; Snap23; Srebf1; Stxbp4; Tgfb1; Trib3; Vamp3; Vapa); генів з високою експресією порівняно з контрольною групою немає. The aim of the work is to determine changes in the expression of genes associated with the course of diabetes under conditions of exposure to intermittent hypoxia in pancreatic tissue samples of Wistar rats. Materials and methods. Analysis of gene expression was used by the polymerase chain reaction method with reverse transcription in real-time using the RT2 Profiler™ PCR Array Rat Diabetes kit (QIAGEN, Germany), where the pancreas of experimental animals was studied. Results. According to the results of the PCR study of animals with experimental diabetes and the influence of hypoxic training on its course, the activity of the studied genes can be divided as follows: genes with low expression compared to the control group of animals, where ΔΔCт <30 (Ace; Cd28; Ctla4; Dusp4 ; Enpp1; Foxp3; G6pc; Gcgr; Glp1r; Gpd1; Gsk3b; Hmox1; Ide; Ikbkb; Il10; Il6; Ins1; Nfkb1; Nkx2-1; Parp1; Pdx1; Pik3cd; Pik3r1; Ppargc1a; Ptpn1; Rab4a; Retn; Slc14a2 ; Snap25; Sod2; Stx4; Stxbp1; Stxbp2; Tnf; Tnfrsf1a; Tnfrsf1b; Ucp2; Vamp2; Vegfa); genes in which no significant changes were detected in the samples in relation to the control group (Acly; Adra1a; Adrb3; Agt; Akt2; Aqp2; Ccl5; Ccr2; Ceacam1; Cebpa; Dpp4; Fbp1; Foxc2; Foxg1; Gcg; Gck; Hnf1b; Hnf4a ; Icam1; Ifng; Igfbp5; Il12b; Il4r; Inppl1; Irs1; Irs2; Mapk14; Mapk8; Neurod1; Nos3; Nrf1; Nsf; Ppara; Pparg; Pygl; Sell; Serpine1; Slc2a4; Snap23; Srebf1; Stxbp4; Tgfb1; Trib3 ; Vamp3; Vapa); there are no genes with high expression compared to the control group. Conclusions. The Nkx2-1 genes, Pik3r1, and Slc14a2 in rats subjected to experimental diabetes displayed notably reduced protein expression activity. Hypoxic training demonstrated an impact on mitigating the expression of the Nkx2-1 protein, which suggests that it might affect the mitochondrial muscle respiratory chain, modulate insulin signaling, and potentially rectify molecular deficiencies associated with diabetic nephropathy. Expression of Dpp4 genes, Gck, Ifng, Mapk8, Nsf and Sell in rats with experimental diabetes and the effect of hypoxic training on it were reduced to the level of control (intact) rats. As a result of the normalization of Dpp4 gene expression, Gck, Ifng, Mapk8, Nsf and Sell may be the influence of the effects of hypoxic training on molecular mechanisms of regulation of hormones and signals related to metabolism and the endocrine system, effects on the immune system and inflammatory processes, as well as insulin resistance.
Analysis of molecular mechanisms of the development of experimental diabetes in Wistar rats under conditions of intermittent hypoxia
ORCID ID: 0000-0001-6617-5178
Keywords: щури лінії Wistar; підшлункова залоза; цукровий діабет; гіпоксична гіпоксія; Wistar rats; pancreas; diabetes; hypoxia